Association between Life's Essential 8 and frailty among the United States older people - Na Zhao; Yameng Fan (Frontiers in Public Health, 2025)
BackgroundThe association between cardiovascular disease health (CVH) and frailty has not been conclusive. The American Heart Association (AHA) has proposed the Life's Essential 8 (LE8) score as an indicator of CVH. We sought to examine the association between LE8 and frailty among older people from the US general population.MethodsWe analyzed data from the 2015–2018 National Health and Nutrition Examination Survey and included older people aged ≥60 years. The LE8 score includes 8 metrics (4 health behaviors and 4 health factors). Frailty status was assessed using the FRAIL scale based on 5 criteria. Multivariate logistic regression analyses were used to assess associations.ResultsA total of 2,511 older people (aged 60 years, with a weighted number of 49,532,259) were included. Among them, 1,294 (weighted percentage: 46.0%) were male and 1,217 (weighted percentage: 54.0%) were female. Older people with a higher LE8 score had a lower risk of frailty, the odds ratio (OR) for each standard deviation (SD) increase in the LE8 score was 0.59 (95% CI, 0.48–0.71, P < 0.001). Similar results were observed in the associations of the health behaviors [OR 0.62 (95% CI, 0.50–0.78), P < 0.001] and health factors [OR 0.76 (95% CI, 0.60–0.96), P = 0.024] with frailty. After excluding older people with poor health status, the results remained significant, the OR for per SD score increase was 0.57 (95% CI, 0.46–0.69, P < 0.001).ConclusionA higher LE8 score was associated with lower risk of frailty among older people in the US. Adherence to optimal CVH scores may be beneficial in helping prevent frailty.